The Effect of Audit Committees on the Sustainability of Financial Inclusion Transactions in Saudi Banks in the Light of the Saudi Vision 2030 - Fallatah, Rasha Abdulrhman (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to examine the relationship between the roles of audit committee and the satiability of financial inclusion in banking sectors in Saudi Arabia. The researcher used the descriptive analytical approach to achieve the aims of the study, and the questionnaire was the tool of the study which applied to (60) of bank employees and managers in Saudi Arabia. The results revealed that there is positive relationship between the role of audit committee in Saudis’ banks and the satiability of financial inclusion with (0.003) less than (0.005) While, there are negative relationship between the satiability of financial inclusion and audit committee meetings, experiences, and the independency of audit committee members (0.400), (0.841) (0.105). Directing the interest of Saudi banks towards designing the objectives of the audit committees in a manner consistent with the requirements of the banking business and in accordance with the goals of Vision 2030.